2020
DOI: 10.1371/journal.pntd.0008732
|View full text |Cite
|
Sign up to set email alerts
|

Non-typhoidal Salmonella infections among children in a tertiary hospital in Ningbo, Zhejiang, China, 2012–2019

Abstract: Background Non-typhoidal Salmonella (NTS), a common cause of diarrheal enterocolitis, may also cause severe invasive diseases. Limited information on NTS infections in children is available in China. Methods We performed a retrospective study of children admitted to the Ningbo Women and Children's Hospital with culture-confirmed NTS infections between January 2012 and December 2019. Clinical and microbiological information were collected. We compared demographic, clinical and antibiotic resistance variables of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
20
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 59 publications
(99 reference statements)
7
20
3
Order By: Relevance
“…In the present study, low level of resistance towards fluoroquinolones (3.92% for ciprofloxacin and 0 for levofloxacin) were observed, which was inconsistent with the findings previously reported in some studies in Uganda and Japan (Kobayashi et al, 2014;Ota et al, 2016). This may be due to the fact that 90.38% (47/52) NTS strains isolated from children aged ≤ 5 years in this study, fluoroquinolones were rarely used in children due to articular toxicity (Ke et al, 2020). Similarly, in a study conducted in China, the prevalence of resistance to ciprofloxacin among NTS isolates was 8.05% (147/1826), and children aged <5 years accounted for 73% (1329/1826) of the overall NTS infections (Liang et al, 2015).…”
Section: Discussioncontrasting
confidence: 99%
“…In the present study, low level of resistance towards fluoroquinolones (3.92% for ciprofloxacin and 0 for levofloxacin) were observed, which was inconsistent with the findings previously reported in some studies in Uganda and Japan (Kobayashi et al, 2014;Ota et al, 2016). This may be due to the fact that 90.38% (47/52) NTS strains isolated from children aged ≤ 5 years in this study, fluoroquinolones were rarely used in children due to articular toxicity (Ke et al, 2020). Similarly, in a study conducted in China, the prevalence of resistance to ciprofloxacin among NTS isolates was 8.05% (147/1826), and children aged <5 years accounted for 73% (1329/1826) of the overall NTS infections (Liang et al, 2015).…”
Section: Discussioncontrasting
confidence: 99%
“…On the basis of the current findings, we recommend against routinely using antimicrobials to treat uncomplicated NTS gastroenteritis in cases of high CRP level. This finding is consistent with that of Mughini-Gras et al (2020) who reported that iNTS isolates were generally less resistant than non-iNTS isolates (Mughini-Gras et al, 2020;Ke et al, 2020). NTS bacteremia in this study tended to develop in young children with prolonged fever.…”
Section: Discussionsupporting
confidence: 92%
“…Approximately 5% of individuals with NTS infection develop invasive diseases, such as bacteremia, meningitis, or septic arthritis, which are especially common in young infants or patients with compromised immune systems ( Hohmann, 2001 ; Feasey et al, 2012 ). Antimicrobial agents are not recommended for non-severe NTS diarrhea, but they are recommended for people at risk of severe or invasive infection ( Ke et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, S. Typhimurium (Group B) and S. Enteritidis (Group D) infections showed the same trend, which was similar to the result of another previous study. 22 However, S. Typhimurium remains the most prevalent serotype, and its prevalence rises annually; many reports are in concordance with our findings, such as those in Ningbo, Zhejiang, China, 23 southern India, 24 Africa, 25 Australia, 16 Thailand and Laos provinces. 26 However, studies from Shanghai, China, 27 and the United States 28 reported that S. Enteritidis was more common than S. Typhimurium.…”
supporting
confidence: 91%